2022
DOI: 10.3390/fermentation8040148
|View full text |Cite
|
Sign up to set email alerts
|

Bioethanol Production Optimization from KOH-Pretreated Bombax ceiba Using Saccharomyces cerevisiae through Response Surface Methodology

Abstract: The present study was based on the production of bioethanol from alkali-pretreated seed pods of Bombax ceiba. Pretreatment is necessary to properly utilize seed pods for bioethanol production via fermentation. This process assures the accessibility of cellulase to the cellulose found in seedpods by removing lignin. Untreated, KOH-pretreated, and KOH-steam-pretreated substrates were characterized for morphological, thermal, and chemical changes by scanning electron microscopy (SEM), thermogravimetric analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…At a high dose of Cu 2+ , Zn 2+ , the growth of S. cerevisiae was completely suppressed. Ghazanfar et al [ 149 ] optimized the physical and nutritional parameters by one factorial at a time (OFAT) and central composite design (CCD), respectively. The study reported that 0.25 g/L yeast extract, 0.25 g/L (NH4) 2 SO 4 , 0.1 g/L K 2 HPO 4 , 0.09 g/L MgSO 4 , 8% substrate, 40 IU/g commercial cellulase, 1% S.cerevisiae inoculum, and pH 5 are optimum for maximum ethanol production (72 g/l) from alkali pretreated Bombax ceiba .…”
Section: Factors Affecting Ethanol Productionmentioning
confidence: 99%
“…At a high dose of Cu 2+ , Zn 2+ , the growth of S. cerevisiae was completely suppressed. Ghazanfar et al [ 149 ] optimized the physical and nutritional parameters by one factorial at a time (OFAT) and central composite design (CCD), respectively. The study reported that 0.25 g/L yeast extract, 0.25 g/L (NH4) 2 SO 4 , 0.1 g/L K 2 HPO 4 , 0.09 g/L MgSO 4 , 8% substrate, 40 IU/g commercial cellulase, 1% S.cerevisiae inoculum, and pH 5 are optimum for maximum ethanol production (72 g/l) from alkali pretreated Bombax ceiba .…”
Section: Factors Affecting Ethanol Productionmentioning
confidence: 99%
“…Various microorganisms from fungi and bacteria can be used to convert sugars into ethanol. Saccharomyces cerevisiae (yeast) is the most commonly used fungus [90], [91], while bacteria that can be used include Zymomonas mobilis, Escherichia coli (E. coli), and Kluyveromyces spp [44], [46], [92]. Then, ethanol as the fermentation product can be separated and purified through the distillation process [52].…”
Section: Bioethanolmentioning
confidence: 99%
“…KOH-pretreated seed pods of Bombax ceiba for ethanol by S. cerevisiae in SSF and SHF were used as second-generation feedstock by Ghazanfar et al [29]. The study shows that the SSF process allows the maximum saccharification (58.6% after 24 h) and highest ethanol yield (57.34 g/L after 96 h) to be obtained.…”
Section: Bioethanol Production From Food Wastementioning
confidence: 99%
“…The SSF process was optimized for physical and nutritional parameters by one factor at a time (OFAT) and central composite design (CCD), allowing to set the optimum fermentation parameters for highest ethanol production (72.0 g/L): 0.25 g/L yeast extract, 0.1 g/L K 2 HPO 4 , 0.25 g/L (NH 4 ) 2 SO 4 , 0.09 g/L MgSO 4 , 8% substrate, 40 IU/g commercial cellulase, 1% Saccharomyces cerevisiae inoculum, pH 5. This study proposed an inexpensive and novel source as a promising feedstock for pilot-scale second-generation bioethanol production [29].…”
Section: Bioethanol Production From Food Wastementioning
confidence: 99%